(untitled) (Sustainability (STPP) Theory, Practice and Policy, 2023)
Karst area has a crucial role in providing water resource. However, due to the intrisic characteristic, water resource in the karst area is highly susceptible to the pollution and relatively hard to manage because the complexity of the aquifer. Karst of Gunung Sewu as one of the main karst area in Indonesia has abundant water resource inside the cave but the utilization is very limited due to the technical constraint to lift the water and distribute it. One the main water resources in Karst of Gunung Sewu is the Pulejajar Underground River at Jepitu Village. As one of the main water resource, a management to maintain its water quality is very important. We examine the water quality of the Pulejajar Underground River and study the factors that affect it. We employ water sampling using purposive sampling in 4 locations and analyze it using Pollution Index (PI) calculation and view the spatial context of the underground river using GIS tool. As the result the PI for the sampling location consists of lighlty polluted in the water intake and the small junction of the Pulejajar Underground River and heavily polluted in the big junction and the Puring Spring. The pollution comes from the Calcium and E. Coli parameter which originates from the dissolution of limestone and the feces of the livestock because the poor filtration at the karst area. The management strategies suppose to comply with the SDGs number 6 as the main framework dan must cover the both side of human side and the nature side including land cover management, water accessibility, and conservation of the catchment area.